Warna Dalam Dokumentasi Travel: Pengaruhnya Terhadap Persepsi dan Memori Wisatawan - Agus Wahyudi; Farhan Ikbar Ferdian; M. Habibie Abdullah S.; Shindi Kusdiana; Faiza Agil Melinia (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research examines an interesting phenomenon in the tourism industry: the perception and memory of tourists and the often misunderstood role of documentation. Although some consider documentation to be less influential and insignificant, this study reveals that for tourism players, the role of documentation is actually very crucial. In the competitive dynamics of the tourism industry, documentation is a vital element in marketing and client acquisition strategies. Travel agencies utilize high-quality documentation as a persuasive tool in their presentations, creating a compelling visual narrative and building trust with potential clients. Documentation is actually a separate service from the travel agency itself, with documentation service providers operating under a standard operating procedure (SOP). This research highlights the complexity of the relationship between documentation, traveler perception, and tourism business dynamics, opening new insights into the importance of visual representation in this highly competitive industry.